2020
DOI: 10.3390/ijerph17239088
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Release by Healthy People during Speaking: Possible Contribution to the Transmission of SARS-CoV-2

Abstract: Our research aimed to review the potential risk of infection by SARS-CoV-2. We used an excerpt of a data set generated in May 2020 for reviewing the SARS-CoV-2 prevention concept of orchestras, singers and actors. People were sampled for droplet release for one-hour activities using a Grimm spectrometer covering a spectrum of 1 to 32 µm diameter. We estimated the number of “quanta” in the exhaled liquid from viral concentrations of 106 to 1011/mL, based on the Human Infective Dose 50 of 218 viral particles. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The difference in the Ct values between nasal swab samples and EBC is linked to the different viral load present in both fluids. ( Eiche et al, 2020 , Giovannini et al, 2021 ). Indeed, it has been postulated that the viral load of SARS-CoV-2 in aerosol samples is several orders of magnitude below those in nasopharyngeal swabs, which are in the order or 6.41 ×10 2 -1.34×10 11 copies/mL ( Giovannini et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the Ct values between nasal swab samples and EBC is linked to the different viral load present in both fluids. ( Eiche et al, 2020 , Giovannini et al, 2021 ). Indeed, it has been postulated that the viral load of SARS-CoV-2 in aerosol samples is several orders of magnitude below those in nasopharyngeal swabs, which are in the order or 6.41 ×10 2 -1.34×10 11 copies/mL ( Giovannini et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Detecting virus content in breath is challenging, especially when the release concentration decreases and the sampling time is limited. Eiche and Kuster estimated the viral concentration in the exhaled liquid from 10 6 to 10 11 /mL ( 39 ) using 5-min EBC, Ma et al reported that earlier stage COVID-19 patients could exhale millions of SARS-CoV-2 particles per hour ( 23 ). The current research results show that later-stage COVID-19 patients could exhale SARS-CoV-2 at below 7,000 copies/min, corresponding to less than one copy per milliliter when considering an average exhale volume of approximately 7,000 mL/min ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of evidence indicating that the survival time of COVID-19 in aerosols ranges from 90 min to three hours, causing the risk of airborne infection [6,27,28] as stagnant air loaded with aerosol droplets in a room with poor ven- COVID-19 is transmitted through aerosolized airborne droplets resulting from the mouth or the nose of an infected person when they breathe, speak, cough, sneeze, or sing in small liquid particles of different sizes ranging from smaller aerosols to larger respiratory droplets. People become infected when the virus enters their noses, mouths, or eyes following close direct contact with an infected person less than one meter away [6,17,[23][24][25][26][27][28][29]. Airborne viral transmission indicates the presence of microbes inside the nuclei of droplets (which are smaller than 5 µmin diameter) that can remain suspended in the air for extended periods of time and can travel over distances of more than one meter.…”
Section: Indoor Environmental Quality Factors (Ieqfs)mentioning
confidence: 99%
“…These aerosols (micro droplets) travel easily in enclosed, crowded and poorly ventilated spaces [6,17,24,28]. There is a lot of evidence indicating that the survival time of COVID-19 in aerosols ranges from 90 min to three hours, causing the risk of airborne infection [6,27,28] as stagnant air loaded with aerosol droplets in a room with poor ventilation may cause people who later enter the room to become infected [29]. This is valid with temperature ranging from C and humidity levels ranging from 65% to 88% according to Azuma et al, 2020 [6].…”
Section: Indoor Environmental Quality Factors (Ieqfs)mentioning
confidence: 99%